2023
DOI: 10.3390/bioengineering10060659
|View full text |Cite
|
Sign up to set email alerts
|

Named Entity Recognition of Diabetes Online Health Community Data Using Multiple Machine Learning Models

Abstract: The rising prevalence of diabetes and the increasing awareness of self-health management have resulted in a surge in diabetes patients seeking health information and emotional support in online health communities. Consequently, there is a vast database of patient consultation information in these online health communities. However, due to the heterogeneity and incompleteness of the content, mining medical information and patient health data from these communities can be a challenge. To address this issue, we b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…At last, the quality of authors suggested SiNER dataset is demonstrated by the potential F1-score of 89.16 produced by the Bi-LSTM-CRF [90] model with character-level descriptions. Xu et al [95] developed the RoBERTa-BiLSTM-CRF(RBC) model for the purpose of locating individuals within the diabetes-relates online health community. The authors used 1889 sample for question-answer texts from Online Good Doctor which is most popular online health community in China.…”
Section: (C) Deep Learning Approachmentioning
confidence: 99%
“…At last, the quality of authors suggested SiNER dataset is demonstrated by the potential F1-score of 89.16 produced by the Bi-LSTM-CRF [90] model with character-level descriptions. Xu et al [95] developed the RoBERTa-BiLSTM-CRF(RBC) model for the purpose of locating individuals within the diabetes-relates online health community. The authors used 1889 sample for question-answer texts from Online Good Doctor which is most popular online health community in China.…”
Section: (C) Deep Learning Approachmentioning
confidence: 99%